1992
DOI: 10.7589/0090-3558-28.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Prerequisites for Oral Immunization of Free-Ranging Raccoons (Procyon Lotor) With a Recombinant Rabies Virus Vaccine: Study Site Ecology and Bait System Development

Abstract: A model baiting system suitable for the delivery of an oral rabies vaccine to freeranging raccoons (Procyon lotor) was developed and tested on barrier islands in South Carolina (USA). Features of barrier island physiography and ecology were studied relative to selective bait deployment and site biosecurity. Capture-mark-recapture data were obtained from 228 raccoons. 93 to 100% of placebo baits were consistently disturbed by 7 days post-bait deployment, and bait acceptance rates by raccoons ranged from 49 to 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 23 publications
2
19
1
Order By: Relevance
“…In this study, 85% of the sampled opossums were tetracycline positive. Hable et al (1992) found similar results; 80% (4/5), and 50% (1/2) of the opossums sampled from Murphy Island (South Carolina, USA) were tetracycline positive. Only one of the 31 cats was tetracycline positive, suggesting that cats do not consume a large number of the vaccine-laden baits.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…In this study, 85% of the sampled opossums were tetracycline positive. Hable et al (1992) found similar results; 80% (4/5), and 50% (1/2) of the opossums sampled from Murphy Island (South Carolina, USA) were tetracycline positive. Only one of the 31 cats was tetracycline positive, suggesting that cats do not consume a large number of the vaccine-laden baits.…”
Section: Discussionsupporting
confidence: 70%
“…Fifty-seven percent of the sampled raccoons were tetracycline positive, which is within the ranges that have been previously reported in placebo trials and the two published vaccine trials (Rupprecht et al, 1987;Perry et al, 1989;Hanlon et al, 1989;Hable et al, 1992;Hanlon et al, 1993Hanlon et al, , 1998Roscoe et al, 1998).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…9 Clinical signs, mortality, pathologic changes, reduced weight gains, serohematologic changes, and reduced immune response have been observed in broiler chicks given rations amended with F. proliferatum culture material that contained defined concentrations of FB 1 , fumonisin B 2 (FB 2 ), and moniliformin or purified FB 1 and moniliformin given individually and in combination (T. Javed et al, unpublished). 5 Prominent gross lesions in affected birds included ascites, hydropericardium, hepatopathy, nephropathy, cardiomyopathy, pneumonitis, gizzard ulceration, and enlarged bursa of Fabricius with grumous material. Because the chicks given the mycotoxin-amended diets had clinical signs (ataxia, reduced weight gain, rough feathering, reduced lymphocyte viability, nephropathy) similar to those associated with vitamin A deficiency, serum vitamin A (retinol) concentrations in the affected chicks were determined, and dose-response effects were evaluated.…”
mentioning
confidence: 99%